Ratio Analysis of HDFC Bank: A Study on Ratio Analysis of HDFC Bank (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Ratio analysis is the very cardinal tool of financial analysis. It defines the relationship between two items of the financial statements of the organization or company. In financial analysis, ratio helps to determine the financial status and performance of the organization. Financial ratio provides the mathematical expressions for the representation of the relationship among the financial statement’s entities. Ratios also help to encapsulate the large financial data of company to tell about the performance and financial performance of the organization. Secondary data has been used by the researcher to achieve the objective of the study. The time period for the data has been studied from 2013-14 to 2017-18.